2019
DOI: 10.1007/s12549-019-00381-8
|View full text |Cite
|
Sign up to set email alerts
|

Fish, amphibian and reptilian assemblage from the middle Miocene locality Gračanica—Bugojno palaeolake, Bosnia and Herzegovina

Abstract: This paper presents the first fossil fish, amphibian and reptilian fauna from Bosnia and Herzegovina Dinarides. The fauna of ectothermic vertebrates of the Bugojno palaeolake, dated to 15.2-14.0 Ma, composes of killifishes (Cyprinodontiformes indet.), a barb (Barbini indet. (aff. Barbus), a crocodile newt (Chelotriton sp.), a painted frog (Latonia sp.) and a crocodile (Alligatoroidea indet. [?Diplocynodon]). The crocodile remains are confined to the lower part of the section corresponding to the swamp deposit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Earlier studies suggested the presence of alligatoroids in the latest Cretaceous of Europe too (Martin, 2007(Martin, , 2010bDelfino, Martin & Buffetaut, 2008), but these taxa (Acynodon, Allodaposuchus) have since been universally recovered outside of Crocodylia (e.g. Narváez et al, 2015), and there is no longer any unambiguous evidence of Diplocynodon remained abundant in western Europe until its last appearance in the middle Miocene, after which no further alligatoroids are known from Europe (Martin, 2010a;Martin & Gross, 2011;Aráez et al, 2017;Rio et al, 2020;Vasilyan, 2020;Chroust et al, 2021).…”
Section: Crocodyloideamentioning
confidence: 99%
“…Earlier studies suggested the presence of alligatoroids in the latest Cretaceous of Europe too (Martin, 2007(Martin, , 2010bDelfino, Martin & Buffetaut, 2008), but these taxa (Acynodon, Allodaposuchus) have since been universally recovered outside of Crocodylia (e.g. Narváez et al, 2015), and there is no longer any unambiguous evidence of Diplocynodon remained abundant in western Europe until its last appearance in the middle Miocene, after which no further alligatoroids are known from Europe (Martin, 2010a;Martin & Gross, 2011;Aráez et al, 2017;Rio et al, 2020;Vasilyan, 2020;Chroust et al, 2021).…”
Section: Crocodyloideamentioning
confidence: 99%
“…The salamandrid Chelotriton is one of the most common taxa in European vertebrate assemblages, spanning the middle Eocene through to the Pliocene (figures 1 and 4c; [8,14,79,[101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120]). According to Marjanović& Witzmann [115], Chelotriton is an early-branching member of the extant salamandrid group Pleurodelinae (the sub-family including all extant 'newts').…”
Section: Eocenementioning
confidence: 99%
“…In the development of the Neogene, the Middle and Upper Miocene were separated (Figure 2), which is divided into seven lithostratigraphic units: basal ( 1 M2,3), the second bottom coal layer ( 2 M2,3), clay, clayey sandstones and marls ( 3 M2,3), first bottom coal layer ( 4 M2,3), marly limestones and marls ( 5 M2,3), main coal layer ( 6 M2,3), clays and sandy clays ( 7 M2,3), Miocene is followed by Pliocene-Quaternary (Pl,Q) and Quaternary (Q) sediments [4,5,6,7,8,9,10,11,12].…”
Section: Geological Characteristics Of the Bugojno Basinmentioning
confidence: 99%